The effectiveness of voice therapy on voice‐related handicap: A network meta‐analysis. (28th June 2020) - Barsties v. Latoszek, Ben; Watts, Christopher R.; Neumann, Katrin
Abstract: Background: Treatment approaches for voice therapy are diverse, yet their differential effects are not well understood. Evaluations of treatment effects across approaches are important for clinical guidance and evidence‐based practice. Objective of review: To quantify the evidence of treatment effectiveness on the outcome measure Voice Handicap Index with the 30‐items (VHI‐30) from existing randomised controlled/clinical trials (RCT) of voice therapy using the statistical approach of a network meta‐analysis (NMA) with a random effects model. Type of review: Meta‐analysis. Search strategy: We searched in MEDLINE (PubMed, 1950 to 2019), Embase (1974 to 2019) and Science Citation Index (1994 to 2019) using five key terms. The inclusion criteria were reports of randomised controlled/clinical trials (RCTs) published in English or German which evaluated the effectiveness of a specific voice therapy treatment using VHI‐30 as an outcome measure in adult participants with non‐organic or organic voice disorders. Studies were excluded if participants had been diagnosed with neurological motor speech disorders or who were vocally healthy. Furthermore, no medical, pharmacological or instrumental (eg voice amplification) treatments were considered. Evaluation method: The primary outcome variable was VHI‐30 with a score from 0 to 120. The pre‐post treatment change in VHI‐30 scores was an average score of 13 points related to various VHI‐30 test‐retest results. Results: We retrieved 464 publications (ie with duplicates) and included 13 RCTs, which evaluated nine interventions, in the final analysis. The most effective intervention with a significant and clinically relevant effect was Stretch‐and‐Flow Phonation (SFP) (mean pre‐post difference −28.37, 95% confidence interval [CI], −43.05 to‐13.68). Resonant Voice (RV), the Comprehensive Voice Rehabilitation Program (CVRP) and Vocal Function Exercises (VFE) also demonstrated significant improvements. Conclusions: Of the nine voice interventions identified with the present NMA, SFP, RVT, CVRP, and VFE effectively improved VHI‐30 scores from pre‐ to post‐treatment. SFP proved to be the most significant and clinically relevant treatment. Further contributions of high‐quality intervention studies are needed to support evidence‐based practice in vocology.